Examining the mediating effects of metabolic syndrome components on the relationship between dairy product consumption and nonalcoholic fatty liver disease in Korean adults - Hyunyu Jeon; Soo-Hyun Kim; Dayeon Shin (PLoS ONE, 2026)
Objective Dairy products are known to improve blood lipid profiles and insulin sensitivity and to reduce risk factors for metabolic syndrome (MetS) and nonalcoholic fatty liver disease (NAFLD). However, the mechanisms through which dairy product consumption influences NAFLD via MetS components remain unclear. This study examined the mediating effects of MetS components on the association between dairy product consumption and NAFLD. Methods This study included 12,775 Korean adults from the Korea National Health and Nutrition Examination Survey (KNHANES) 2019–2021. Dairy product intake was assessed using a 24-hour dietary recall. NAFLD was defined using a hepatic steatosis index score >36, and MetS was classified according to the National Cholesterol Education Program Adult Treatment Panel III criteria. Multivariable logistic regression analyses were conducted to examine the associations among dairy intake, NAFLD, and MetS components. Mediation analyses with bootstrapping (n = 1,000) were performed to investigate the mediating effects of individual MetS components on the association between dairy consumption and NAFLD. Results Consumption of more than one serving of dairy products was associated with a lower prevalence of NAFLD among women (adjusted odds ratio [AOR], 0.75; 95% confidence interval [CI], 0.59–0.96). Regarding MetS components, intake of one serving of dairy products was associated with lower odds of elevated triglycerides in men (AOR, 0.75; 95% CI, 0.63–0.89). In women, consumption of at least one serving was associated with decreased hyperglycemia (AOR, 0.84; 95% CI, 0.73–0.97), abdominal obesity (AOR, 0.69; 95% CI: 0.55–0.87), low high-density lipoprotein cholesterol (AOR, 0.83; 95% CI: 0.72–0.95), and elevated triglyceride levels (AOR, 0.71; 95% CI, 0.60–0.85). Mediation analyses indicated that, among women, significant proportions of the associations between dairy product consumption and NAFLD were mediated by waist circumference (58.0%), systolic blood pressure (18.2%), and high-density lipoprotein cholesterol (51.7%), whereas no significant mediation effects were observed among men. Conclusions Dairy product consumption was associated with a lower prevalence of MetS and NAFLD among women. Mediation analysis further suggested that dairy product consumption may reduce the risk of NAFLD by improving metabolic dysfunction among women.